1991
DOI: 10.1007/bf02745091
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity of doped ZnS

Abstract: The electrical conductivity of doped ZnS with different impurities (Mn, Fe, Co, Ni and Cu) of various concentrations has been measured to verify the existence of ladderlike levels of 'killers' of luminescence. Attempts have been made to ascertain the separation between-the valence band of the host ZnS and the ground state of the accepter impurities and also to investigate the effect of various concentrations of impurities on the electrical conductivity of doped ZnS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…From this figure, it has been observed that as the impurity concentration is increased, conductivity first increases (the samples 50.01 and S0.1) and then the trend reverses (the samples S1 and S2). A similar kind of behaviour has been observed in the case of ZnS doped with Fe and Cu [6]. The increase of conductivity with increasing concentration of impurity up to a certain level may be attributed to an increase in the number of charge carriers [7].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…From this figure, it has been observed that as the impurity concentration is increased, conductivity first increases (the samples 50.01 and S0.1) and then the trend reverses (the samples S1 and S2). A similar kind of behaviour has been observed in the case of ZnS doped with Fe and Cu [6]. The increase of conductivity with increasing concentration of impurity up to a certain level may be attributed to an increase in the number of charge carriers [7].…”
Section: Resultssupporting
confidence: 75%
“…The samples were labelled according to the dopant concentrations, for example the sample S0.01 had 0.01 mole % of Coe+ impurity ions. The other details regarding the sample synthesis are similar to those reported earlier [6]. The resistivity measurements between room temperature (RT) and 1000 K were performed by the two-probe method.…”
Section: Methodsmentioning
confidence: 99%
“…The luminescent properties of the various metal doped ZnS nanoparticles, nanowires and nanobelts were extensively investigated [17,18]. ZnS based DMS also show electrical [19], magnetic [18] and optical properties [20].…”
Section: Introductionmentioning
confidence: 99%